The case of myelodysplastic syndrome after 65 years old - Paulina Kasperska; Eliza Oleksy; Anna Ziółkowska; Wojciech Stemplowski; Remigiusz Sokołowski; Karolina Klimkiewicz-Wszelaki; Katarzyna Piotrowska; Kornelia Kędziora-Kornatowska; Walery Zukow (Kazimierz Wielki University, 2019)
Background. The etiology of MDS syndromes (myelodysplastic syndromes) is unknown. MDS is a disease of the elderly, mostly affects people over 50 years of age. Elderly patients with MDS are diagnosed at an earlier stage of the disease compared to younger people. Therapeutic options in MDS include treatment with high-dose chemotherapy with / without hematopoietic stem cell transplantation, treatment with low-dose chemotherapy, supportive care and symptomatic treatment. Transfusion of RBC (Red Blood Cells) concentrate and platelet concentrate is used in the majority of patients with MDS and it is the only form of therapy recommended for both patients with good and bad prognosis. Case report. A 77-year-old patient repeatedly hospitalized in the Clinic of Geriatrics for symptomatic anemia in myelodysplastic syndrome. Independent patient in the field of self-care, living alone. Patient take many medicines from different groups. Patient with multidisease. Symptoms of the patient: weakness, depressed mood, reduced tolerance of physical exercise, dizziness, palpitations associated with slight physical effort, symptoms of gastrointestinal bleeding, stenocardial complaints in 2017. A bone marrow biopsy was performed - in the myelogram MDS was diagnosed with features of low-grade triplicate dysplasia. Patient repeatedly hospitalized for transfusion of Irradiated Leukocyte-Depleted RBC Concentrate (since the beginning of 2018 11 times - average 1 x / month). From October 2012 to November 2018, a total of 49 Irradiated Leukocyte-Depleted RBC Concentrates units were transfused, reducing only the symptoms of the disease. Results. A careful assessment of the functional status, ability to tolerate treatment, disease progression and overall health can be helpful in determining treatment. To improve access to treatment, emphasis should be placed on oral drug therapies that can be easily administered on an outpatient basis to minimize transfusion. Palliative care and environmental care are important aspects of improving the health and quality of life of MDS patients.